GENE-56. MENINGIOMA GENOMIC SUBGROUP AS A PREDICTOR OF POST-OPERATIVE PATIENT OUTCOMES: IMPLICATIONS FOR TREATMENT AND FOLLOW-UP. (11th November 2019) - Youngblood, Mark; Sheth, Amar; Zhao, Amy; Montejo, Julio; Duran, Daniel; Li, Chang; Tyrtova, Evgeniya; Özduman, Koray; Peyre, Matthieu; Boetto, Julien; Omay, Sacit; Kalamarides, Michel; et al.
Abstract: BACKGROUND: Meningiomas can be classified into six genomic subgroups based on mutations in NF2, SMARCB1, KLF4, POLR2A, or activating variants in the PI3K or Hedgehog signaling pathways. Previous work has identified specific associations of driver events with clinical and molecular features, such as tumor location. However, their utility in predicting post-operative patient outcomes is not well-explored. Similar to recently described epigenetic signatures, underlying genomic subgroup may provide prognostic value in meningioma management. METHODS: Targeted sequencing data was used to classify over 500 meningiomas into established genomic subgroups, and available patient outcome data was assembled based on retrospective chart reviews. Collected data included recurrence (based on imaging), extent of resection (EOR), use of post-operative radiation, and radiologic follow-up period. Statistical associations between genomic subgroup and recurrence were assessed using Fisher's exact, Kaplan-Meier, and Cox proportional hazards modeling, including stratification based on use of radiation, EOR, grade, and location. RESULTS: Meningiomas in the PI3K subgroup exhibited higher rates of early recurrence during the first five post-operative years. This subgroup affiliation was found to be an independent predictor of recurrence free survival from Ki-67, grade, and other clinical features. By contrast, recurrence was rare in the POLR2A, SMARCB1, and KLF4 subgroups, and was typically associated with use of post-operative radiation in these cases. The longest average recurrence free survival was observed in POLR2A mutant meningiomas. CONCLUSIONS: Our analysis identifies divergence in meningioma patient outcomes based on genomic subgroup and suggests patients with PI3K activating events may require closer surveillance. These tumors, which often occur near and encase critical neurovascular structures along the sphenoid wing, may further benefit from consideration of radiation and emerging precision therapies. Conversely, other subgroups rarely recur, suggesting caution be invoked with use of potentially morbid adjuvant treatment.